UP assembly elections: caste dominates ideology - Verma A.K. (2002)
Analysis of the February 2002 assembly elections in UP and their outcome: the issues, the division of seats among the electoral alliances, the composition of candidates of different parties, the gains and losses of the parties in terms of seats and vote shares for the whole state and for different regions, voter preferences for parties by caste and other characteristics and the impact of the election campaigns on the performance of the parties. - Reproduced.
Keywords: Uttar Pradesh. Legislative Assembly - Elections; Elections - India - Uttar Pradesh; Uttar Pradesh - Politics and government; Politics and government